Plagiarism phenomenon in European countries: results from GENIUS Project - Dias, Paulo C. (2021)
The present study aims to explore 170 teachers and 334 secondary school student's perceptions on plagiarism of seven European countries. Results indicate that both know that plagiarism is illegal; attribute plagiarism to the easiness on contents access on Internet but while teachers tend to attribute causes to student's lack of skills, students highlight the pressure to get good grades, laziness and poor management as well as the expectation that won’t be caught. To prevent plagiarism while teachers suggest to promote student's skills, students focus on pedagogical issues. Similarities and differences are explored as well as the possible effects and implications.